2014
DOI: 10.1093/beheco/aru035
|View full text |Cite
|
Sign up to set email alerts
|

No relationship between female emergence time from the roosting place and extrapair paternity

Abstract: In several bird species, the period around dawn seems important for extrapair behavior. For example, a study on great tits (Parus major) showed that females that emerged earlier from their roosting place during the peak of their fertile period were more likely to have extrapair young in their brood. We investigated the potential effect of female emergence times on extrapair behavior in the blue tit (Cyanistes caeruleus). First, we tested the relationship between natural female emergence times from the nest-box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
4
42
0
1
Order By: Relevance
“…While our study necessarily collected timing data after the decision to lay eggs had been made, we believe that our findings are indicative of an individual's chronotype prior to nest initiation. Other studies, including in our study species, have also observed within year consistency in individual female awakening and nest departure times both during and outside the breeding season (Steinmeyer et al 2010;Schlicht et al 2014;Stuber et al 2015). In addition, onset of activity for 6 dark-eyed junco females in our study was collected during a known second nesting attempt.…”
Section: Discussionsupporting
confidence: 59%
“…While our study necessarily collected timing data after the decision to lay eggs had been made, we believe that our findings are indicative of an individual's chronotype prior to nest initiation. Other studies, including in our study species, have also observed within year consistency in individual female awakening and nest departure times both during and outside the breeding season (Steinmeyer et al 2010;Schlicht et al 2014;Stuber et al 2015). In addition, onset of activity for 6 dark-eyed junco females in our study was collected during a known second nesting attempt.…”
Section: Discussionsupporting
confidence: 59%
“…Return latency and number of visits were square‐root transformed to improve model fit. Because females show marked delays in morning emergence and advances in roosting time once egg laying has commenced (Schlicht et al, ), we restricted these analyses to the period before laying started (thus excluding the day on which the first egg was laid).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that carryover effects on the start of dawn singing are absent. Of course, the light treatment might still have led to a carryover effect on awakening time (see Schlicht et al, 2014). A similar pattern of light entrainment was found in a study of captive great tits: onset of activity gradually advanced during the illuminated days of the experimental period but it immediately returned to normal during the following control period ( For the robin, the estimated effect size in response to the experimental treatment (37 min; Table 1) was higher than the effect size previously reported in a correlational study conducted in the same general area (Da Silva et al 2014: mean and 95% CI: 19 min [9e29 min]), However, another correlational study showed an advance in the start of singing of 64 min under artificial light conditions (Kempenaers et al, 2010), and we note that in Da Silva et al (2014) some robins started singing before the recordings started (1.5 h before sunrise).…”
Section: ; Damentioning
confidence: 99%
“…If the experimental light had such an effect on the diel rhythm of individuals, we should observe a progressive return to natural times of dawn chorus initiation during consecutive dark days. Such carryover effects have been shown for the timing of emergence from the roost in female blue tits, Cyanistes caeruleus, that were experimentally exposed to night light (Schlicht, Valcu, Loes, Girg, & Kempenaers, 2014). We also tested whether the light effect becomes progressively stronger after the control 'treatment' (dark phase), and for simplicity also refer to this as a 'carryover' effect.…”
mentioning
confidence: 93%